Application of microemulsions for the removal of synthetic resins from paintings on canvas. Issue 7 (3rd April 2019) - Guizzo, Sara; Tortolini, Cristina; Pepi, Federico; Leonelli, Francesca; Mazzei, Franco; Di Turo, Francesca; Favero, Gabriele
Abstract: Traditional cleaning methods with organic solvents often are not suitable for removal of aged resin so researchers have to find new formulations. In this work, a case study is reported in which new microemulsions were applied on the surface of a painting covered by some aged resin layers used during a previous restoration. Based on the quality of the intervention and the analysis of a sample of the varnish carried out with both MALDI-TOF and ATR-IR spectrometers, it was conjectured that this undesired material could be an acrylic polymer. So it was chosen to use xylene, ethyl acetate and propylene carbonate (XYL and EAPC) microemulsions (O/W oil in water). The first is able to solubilise only acrylic polymers, the second may solve both acrylic and vinyl resins. The first has had the greatest effect allowing complete varnish removal and original artwork restoration. Abstract :